New class of bacterial quorum sensing antagonists: glycomonoterpenols synthesized using linalool and alpha terpineol - Mukherji, Ruchira; Prabhune, Asmita (World Journal of Microbiology & Biotechnology, 2015)
With increasing burden of antibiotic resistant microorganism search for newer drug targets and potent drug molecules is a never ending scenario. Quorum sensing (QS), the phenomenon of bacterial cross-talk, is one such target that has captured the attention of many and has been touted as the future of new age antimicrobials. Quorum sensing has the potential to regulate a plethora of bacterial virulence phenotypes and search of molecules with powerful quorum sensing inhibitory (QSI) capacity are underway. Monoterpene alcohols like linalool and alpha terpineol have been shown to possess antimicrobial and anti-biofilm activity. However in this article we attempt to bring forth a new class of compounds, glycomonoterpenols, derived from monoterpenoids alcohols. These glycomonoterpenols have been synthesized using Candida bombicola ATCC 22214 by feeding the cells with linalool and alpha terpineol respectively as substrates in 10 % glucose, production medium. The advantage of these molecules over their parent compound is their additional surfactant like property, increased solubility and enhanced QSI potential. A variety of gram-negative bacteria capable of elaborating quorum sensing mediated phenotypes have been selected and both these glycoterpenoid derivatives have been shown to possess strong anti-QS activity.
Keywords: Alpha-terpineol; Glycomonoterpenols; Linalool; Pseudomonas aeruginosa; Quorum sensing inhibition